Anticipatory and Compensatory Postural Adjustments in Sitting and Standing Positions During Functional Activities in Children With Cerebral Palsy. - Vasani, Priyal; Narayan, Amitesh; Nayak, Akshatha; Alsulaimani, Mohammed; Alzahrani, Abdul Rahman (Physiotherapy Research International, 2025)
Background and purpose: Anticipatory postural adjustments (APA) and compensatory postural adjustments (CPA) have played a vital role in postural control since early childhood, which is critical to accomplishing activities in daily life. However, literature indicated dissimilarities and inconsistencies in APA and CPA analysis in sitting and standing positions in children with Cerebral Palsy (CP). Thus, this study analyzed the changes in postural control (APA and CPA) through the postural muscles [rectus abdominis (RA) and erector spinae (ES)] in both standing and sitting positions during functional activities (grasping a ball) in children with CP. Methods: Children with CP [N = 21] aged 5–13 years having GMFCS levels I (n = 12) and II (n = 9) participated. Surface electromyography (EMG) was performed for postural muscles (ES and RA) to measure the APA and CPA with two types of loads (heavy and light) in both sitting and standing positions. Results: Children with CP showed increased EMG amplitude for APA and CPA with a heavier load than light load in sitting and standing positions. The EMG amplitude of CPA in sitting and standing for both load conditions was significantly higher than that of APA. Discussion: The findings suggest rehabilitation programs should enhance APA and CPA through targeted exercises and load management strategies. These insights have the potential to inform clinical practices, improve postural stability, and ultimately strengthen the ability of children with CP to perform daily activities with greater ease and confidence, thereby significantly impacting the quality of life.